The The Circulating Visfatin Level Relation to the Severity of Chronic Kidney Disease - Korzh, Oleksii; Titkova, Anna; Fylenko, Yana (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Adipokines have been associated with atherosclerotic heart disease, which has plenty of common risk factors with chronic kidney disease (CKD), but their association with CKD has not been well characterized. AIM: We investigated the association between the serum visfatin level and CKD. METHODS: The serum visfatin levels in 101 CKD patients and 101 controls were compared. CKD was defined as estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2 or presence of albuminuria (≥30 mg/24 h). RESULTS: After adjustment for established CKD risk factors, the median (interquartile range) of the serum visfatin was 3.65 ng/ml (2.31–4.59) in patients with CKD and 1.66 ng/ml (0.90–2.45) in controls without CKD (p < 0.0001 for group difference). Serum visfatin was significantly and inversely correlated with eGFR (r = –0.79, p < 0.0001) and positively correlated with urine albumin (r = 0.71, p < 0.0001) in the study participants. There was a strong dose-response and the significant relationship between serum visfatin level and CKD severity, assessed by GFR and albuminuria, regardless of established risk factors for CKD, including hypertension, diabetes, and cardiovascular disease. CONCLUSION: Our results show that circulating visfatin is associated with the risk and severity of CKD. These results suggest that longitudinal studies and clinical trials should be conducted to investigate if adipocytokines play a role in the development and progression of CKD independent of body mass index or waist circumference. These important findings may advance our further understanding of CKD risk factors.